Toward An Islamic Administrative Theory (American Journal of Islam and Society, 1987)
IntroductionA comprehensive Islamic theory that can offer complete guidance forIslamic organizations and help clarify the behavior of organizations, groups,and individuals is yet to be developed. However, there are many rules relatingto administration which are scattered throughout different Islamic sources.These rules were utilized in early Islamic society, but were never organizedunder specific management concepts as is the case in contemporary managementthought. The quest in recent years for such a theory has been intense,and there have been frantic efforts by researchers to group different administrativeguidelines from Islamic sources with the intention of formingan Islamic administrative paradigm, herein called a theory, although it is nota complete theory.Ahmed Ibrahim Abu Sin, for example, has tried to identify the basic particularsor postulates of Islamic administrative theory in his book The IslamicAdministration (1981). He maintains that the characteristic feature of Islamictheory is its emphasis on all the variables and factors that affect the administrativecycle in an organization and its understanding of individualbehavior in light of social and cultural forces. Islamic theory sees no separationbetween ethics, morality, and administration. The same applies to thelarger Islamic society of which administration is a subsystem.The basic postulates of Islamic theory and the variables it emphasizes includethe following:(1) Islamic administrative theory should be closely connected to the socialphilosophy of the Islamic system and enforce the moral principles of the largerIslamic society. (This point is discussed in greater detail below.)(2) Islamic administrative theory should take into consideration economicvariables and strive to fulfill individuals’ physiological needs ...